Vitamin D in sports: what has been shown? (Research, Society and Development, 2020)
Introduction: vitamin D deficiency is considered a public health problem with high global prevalence. Many studies have found low levels of this vitamin in athletes. And in the midst of this growing prevalence, the scientific area has shown a greater interest in studying the role of vitamin D in addition to bone tissue, specifically muscle tissue, which expresses receptors for this vitamin. Objective: to seek scientific evidence on the possible effects and benefits of vitamin D in exercise. Methodology: this work is an integrative review of the literature. The search for the articles was carried out in the PubMed database, including original articles of the last 10 years carried out only with athletes. This review consists of 33 original articles. Results: it was observed that the results of the studies regarding sports practice varied widely, there were articles that demonstrated positive and statistically significant results and studies that did not verify any association or improvement of the to post-intervention training or observational analysis of vitamin D supplementation. Conclusion: in fact, vitamin D in sports practice has been widely studied in scientific circles, but you can not to affirm in a consensual way the real effects that their supplementation or maintenance of the adequate levels provide to the athletes, being necessary more studies so that in the future a more consistent vision is possible on the role of vitamin D in the sport performance.